Articulate storyline-based interactive learning media with character values on natural science learning for 10-11 years old students - Nur Indah Rahmawati; Ida Fiteriani; Rahma Diani (Online Learning In Educational Research (OLER), 2022)
This research was inspired by the underutilized use of character-laden media in science education. The goal of this research is to create character-based interactive learning media on the material properties and changes in the shape of objects using the Articulate Storyline. Also, to test the feasibility and responses of teachers and students toward the developed product. The research method used was development (Research and Development) adopted from Borg and Gall. This research was carried out in three different schools. Techniques for gathering data include interviews, surveys, and recordkeeping. The data analyses employed were qualitative and quantitative methods. The product validation results were quite suited for usage, with the percentages of feasibility values of 84.16 by linguists, 88.87 by material experts, and 94 by media experts. The response percentages by teachers and students were 85.2 and 91.1, respectively. The product developed was well-suited for use in the fifth-grade science learning process. It is hoped that additional research will be conducted using other materials to examine the efficiency of this media, particularly in improving character values.